(untitled) (Bangladesh Journal of Agriculture, 2022)
Thirty-six genotypes of chilli (Capsicum sp.) were evaluated at the Regional Spices Research Centre, BARI and Gazipur during February 2017 to November 2018 to identify the promising genotype(s) for variety development process. Distinct variation among the genotypes was observed in all the qualitative parameters except seed color and fruiting behavior. The genotype CO 525 and CO 631 took relatively short times for the 1st flower bud opening showing 44 and 42 days respectively, while the genotype CO 633 & CO 648 took 125 & 110 days for the 1st flowering and 130 and 141 days for the first fruit set Plant height ranged from 47.02 cm (CO 002) to 111.35cm (CO 525). The maximum number of primary branches was recorded in CO 648 (11.33/plant) and the lowest in CO 630 (4.00/plant). Single fruit weight ranged from 1.46 g (CO 626) to 11.70 g (CO 631) while fruit length varied from 2.90 cm (CO 645) to 10.63 cm (CO 002 & CO 631). Pedicel length was longest in CO 643 (5.06 cm) and shortest in CO 639 (1.53 cm). The highest pericarp thickness was recorded from CO 640 (4.72 mm) and the lowest in CO 635 (0.63 mm). The larger weight of pericarp was obtained from CO 640 (6.00 g) and the smaller from CO 645 (0.24 g). The genotype CO 631 had the maximum number of fruits/plant (308.00) and the genotype CO640 had the minimum number of fruits/plant (38.00). The genotype CO 631 produced the maximum weight of fruits/plant (606.43 g) which was identical to CO 525 (465.50 g/plant). The highest number of fresh seeds was obtained from CO 631 (89.66/fruit) and it was the lowest in C0 646 (20.33). The highest weight of fresh seeds/fruit was obtained from CO 631 (0.63 g) and the lowest from CO 645 (0.11 g). The genotypes CO 631 had the maximum 1000-fresh seed weight (5.20 g) which was statistically similar to BARI Chilli-2 and the minimum in CO 647 (1.50g). The maximum fruit yield was recorded with CO 631 (23.04 t/ha) followed by CO 525-1 (18.25 t/ha), CO 5251 (17.69 t/ha), CO 003 (17.13 t/ha), respectively while it was minimum in CO 002 (4.65 t/ha). The results revealed that the genotypes significantly differed in most of the parameters which offers a good scope for selection of better genotypes as parents for the desired traits. Bangladesh J. Agri. 2019-2021, 44-46: 65-76